A case of resistance to tyrosine kinase inhibitor therapy: small cell carcinoma transformation concomitant with plasma-genotyped T790M positivity. Issue 9 (October 2017) - Xu, Yanjun; Huang, Zhiyu; Gong, Lei; Fan, Yun
Abstract : Although non-small-cell lung cancer patients with epidermal growth factor receptor (EGFR) mutations are responsive to EGFR-tyrosine kinase inhibitors, drug resistances are always inevitable. The secondary somatic EGFR threonine–methionine substitution at position 790 (T790M) mutation accounts for ∼50% of acquired resistance mechanisms. Small cell lung cancer (SCLC) transformation is a relatively rare mechanism, but has recently attracted considerable attention. The coexistence of both the mechanisms in one patient is much more scarce in clinic. In this case report, we described a 37-year-old woman who underwent refractory after second-line gefitinib therapy and was confirmed to have SCLC transformation without the T790M mutation in the left lobar nodule, but concomitant with the plasma-genotyped EGFR T790M mutation. Our case report uncovered the underling relationship between SCLC transformation and the T790M mutation, and the fluid biopsy approach may help overcome the problem of heterogeneity in acquired resistance to EGFR-tyrosine kinase inhibitors.